Long non-coding RNAs are involved in the crosstalk between cancer-associated fibroblasts and tumor cells - Yang, Chenbo; Shu, Jiao; Li, Yiwei; Zhao, Na; Liu, Xiaonan; Tian, Xiangyu; Sun, Zexin; Tabish, Muhammad Saud; Hong, Yichen; Chen, Kuisheng; Sun, Miaomiao (Frontiers in Immunology, 2024)
The proliferation of tumors is not merely self-regulated by the cancer cells but is also intrinsically connected to the tumor microenvironment (TME). Within this complex TME, cancer-associated fibroblasts (CAFs) are pivotal in the modulation of tumor onset and progression. Rich signaling interactions exist between CAFs and tumor cells, which are crucial for tumor regulation. Long non-coding RNAs (LncRNAs) emerge from cellular transcription as a class of functionally diverse RNA molecules. Recent studies have revealed that LncRNAs are integral to the crosstalk between CAFs and tumor cells, with the capacity to modify cellular transcriptional activity and secretion profiles, thus facilitating CAFs activation, tumor proliferation, metastasis, drug resistance, and other related functionalities. This comprehensive review revisits the latest research on LncRNA-mediated interactions between CAFs and tumor cells, encapsulates the biological roles of LncRNAs, and delves into the molecular pathways from a broader perspective, aspiring to offer novel perspectives for a deeper comprehension of the etiology of tumors and the enhancement of therapeutic approaches.